Effects of supplemental octanoate on hepatic lipid metabolism, serum biochemical indexes, antioxidant capacity and inflammation-related genes expression of large yellow croaker (Larimichthys crocea) fed with high soybean oil diet - Zhao, Manxi; Zhang, Zhou; Liu, Yongtao; Zhang, Wencong; Gong, Ye; Tang, Yuhang; Chen, Fan; Zhang, Jianmin; Liu, Guobin; Zhang, Haitao; Li, Yueru; Mai, Kangsen; et al. (Frontiers in Immunology, 2023)
Dietary high soybean oil (SO) levels might cause hepatic lipid deposition, induce oxidative stress and inflammatory response in aquatic animals, while octanoate (OCT) is beneficial to metabolism and health in mammals. However, the effect of OCT has been studied rarely in aquatic animals. In this study, a 10-week feeding trial was conducted to investigate the effect of supplemental OCT on hepatic lipid metabolism, serum biochemical indexes, antioxidant capacity and inflammatory response of large yellow croaker (Larimichthys crocea) fed with high SO levels diet. The negative control diet contained 7% fish oil (FO), while the positive control diet contained 7% SO. The other four experimental diets were supplemented with 0.7, 2.1, 6.3 and 18.9 g/kg sodium octanoate (OCT) based on the positive control diet. Results showed that OCT supplementation effectively reduced the hepatic crude lipid, triglyceride (TG), total cholesterol (TC) and non-esterified free fatty acids contents, and alleviated lipid accumulation caused by the diet SO. Meanwhile, OCT supplementation decreased the serum TG, TC, alanine transaminase, aspartate transaminase and low-density lipoprotein cholesterol levels, increased the serum high-density lipoprotein cholesterol level, improved the serum lipid profiles and alleviated hepatic injury. Furthermore, with the supplementation of OCT, the mRNA expression of genes related to lipogenesis (acc1, scd1, fas, srebp1, dgat1 and cebpα) and fatty acid (FA) transport (fabp3, fatp and cd36) were down-regulated, while the mRNA expression of genes related to lipolysis (atgl, hsl and lpl) and FA β-oxidation (cpt1 and mcad) were up-regulated. Besides that, dietary OCT increased the total antioxidant capacity, activities of peroxidase, catalase and superoxide dismutase and the content of reduced glutathione, decreased the content of 8-hydroxy-deoxyguanosine and malondialdehyde and relieved hepatic oxidative stress. Supplementation of 0.7 and 2.1 g/kg OCT down-regulated the mRNA expression of genes related to pro-inflammatory cytokines (tnfα, il1β and ifnγ), and suppressed hepatic inflammatory response. In conclusion, supplementation with 0.7-2.1 g/kg OCT could reduce hepatic lipid accumulation, relieve oxidative stress and regulate inflammatory response in large yellow croaker fed the diet with high SO levels, providing a new way to alleviate the hepatic fat deposition in aquatic animals.